State Formation in Early Modern Alsace, 1648-1789 - Lazer, Stephen A., 1983- (Book collections on Project MUSE., 2019)
"A documented study of early modern state formation, sovereignty, legitimacy, and comparative political culture in Alsace between the Peace of Westphalia and the French Revolution"--